MECHANISMS IN ENDOCRINOLOGY: Clinical and pharmacogenetic aspects of the growth hormone receptor polymorphism. Issue 6 (December 2017) - Boguszewski, Cesar L; Barbosa, Edna J L; Svensson, Per-Arne; Johannsson, Gudmundur; Glad, Camilla A M
Abstract : Pharmacogenetics aims to maximize the beneficial effects of a medical therapy by identifying genetic finger prints from responders and non-responders and, thereby improving safety and efficacy profile of the drug. Most subjects who are deficient in growth hormone (GHD) are candidates for recombinant human GH (rhGH) therapy. To date, it is well established that even after adjustments for several clinical variables, such as age, gender, body composition and the age at onset of the GHD, response to rhGH treatment is highly variable among individuals, part of which is believed to be due to genetic factors within the GH system. As the first genetic variant to potentially influence the individual response to rhGH therapy in children with growth disorders, polymorphism in the GH receptor (GHR) has attracted a great interest as a target for pharmacogenetics. Studies have been conducted to compare the functional and molecular effects of the full-length GHR (fl-GHR) isoform with the exon 3 deleted (d3-GHR) isoform in children and adults treated with rhGH therapy. Additionally, the impact of the GHR polymorphism has been investigated in relation to the clinical status and response to medical treatment in acromegaly, especially to the GHR antagonist drug pegvisomant. We have performed a narrative review of the studies performed to date on the association of GHR polymorphism with rhGH response in children and adults, and its potential influence in the medical management of acromegaly. In addition, data from studies on the general population and in other chronic diseases examining a role of this genetic variant in the regulation of growth and metabolism are summarized.